2001
DOI: 10.1111/j.1574-695x.2001.tb01565.x
|View full text |Cite
|
Sign up to set email alerts
|

Formulations of single or multiple H. pylori antigens with DC Chol adjuvant induce protection by the systemic route in mice Optimal prophylactic combinations are different from therapeutic ones

Abstract: The ability to induce a protective response against Helicobacter pylori infection has been investigated by systemic immunization of mice with urease formulated with the cationic lipid DC Chol. This compound acts both as a formulating agent and as an adjuvant and induces a balanced Th1/Th2 response shown to be more effective for protection in our previous studies. Urease-DC Chol induced a significant protection in prophylaxis but not in therapeutic immunization. The protection level was between 1.5 and 2 log re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In the various preclinical animal models, vaccination has been shown to protect against H. pylori challenge infection [10]. Most of vaccines tested so far contain only one or two antigens, although recent studies suggested that combining several protective antigens could substantially increase vaccine efficacy [6,11,12]. Characterization of protein differences between strains may be of particular significance, indicating proteins which could be important as strain markers associated with specific clinical outcomes of H. pylori infection.…”
Section: Introductionmentioning
confidence: 96%
“…In the various preclinical animal models, vaccination has been shown to protect against H. pylori challenge infection [10]. Most of vaccines tested so far contain only one or two antigens, although recent studies suggested that combining several protective antigens could substantially increase vaccine efficacy [6,11,12]. Characterization of protein differences between strains may be of particular significance, indicating proteins which could be important as strain markers associated with specific clinical outcomes of H. pylori infection.…”
Section: Introductionmentioning
confidence: 96%
“…Hop B and Hop C are considered potential targets for vaccine therapy as they are involved during the early colonization stages of infection with H. pylori. In immunization studies in mice, when HopB, either on its own or in combination with other antigens (BabB, urease, catalase), was conjugated to the DC-Chol mucosal adjuvant, enhanced cellular and humoral protective responses were observed [208]. In a further promising evaluation of HopB immunogenicity in recombinant plasmids, HopB recombinant protein was introduced as a novel means of infection prophylaxis and eradication [209].…”
Section: Table 2 Improvement Of Vaccine Design and Progression Of Dev...mentioning
confidence: 99%
“…Hop B and Hop C are considered potential targets for vaccine therapy as they are involved during the early colonization stages of infection with H. pylori. In immunization studies in mice, when HopB, either on its own or in combination with other antigens (BabB, urease, catalase), was conjugated to the DC-Chol mucosal adjuvant, enhanced cellular and humoral protective responses were observed [185]. In a further promising evaluation of HopB immunogenicity in recombinant plasmids, HopB recombinant protein was introduced as a novel means of infection prophylaxis and eradication [186].…”
Section: Targeting Outer Membrane Proteinsmentioning
confidence: 99%